Understanding ITO decisions and implementations in Malaysia public healthcare sector: the evidence from a pilot case study - Arshad, Yusri; Ahlan, Abdul Rahman (2011)
As IT Outsourcing (ITO) grows in complexity, there is a call for effective management of ITO relationship to reduce risks. ITO relationship receives a lot of attention from researchers recently. Many studies, however, are conceptual or hypothesis-testing in nature. In addition, no one study focuses on full and comprehensive ITO decisions and implementations using Simon’s stage model as a framework of inquiry. Thus, this study adopts case study research and grounded theory to investigate in detailed the ITO decisions and implementations of a pilot case in Malaysia public sector. In addition, we perform literature review, websites, documents, news as well as interviews. Our findings indicate that Malaysia practice is not much difference from developed countries except for the Asian cultural values still a dominant factor in local service providers. The research finds that public sector lacks IT resources competences and capabilities while relationship exchange varies from one case to another. Many working relationship factors are generated from iterative data reduction processes. Hence, this study contributes to literature as well as Malaysian ITO practical reference for business managers.